Knowledge Regarding Blood Donation among Students of a College in Western Nepal - Bhandari, Sita; Nepal, Parbati; Pokharel, Bandana (Journal of Lumbini Medical College, 2020)
Introduction: Blood can save millions of lives, and young people are the hope and future of safe blood supply worldwide. This study was conducted with an objective to assess knowledge level regarding blood donation among college students.Methods: A cross sectional study was conducted at Shree Mandavya Multiple Campus, Palpa, among all years of Bachelor in Business Studies students. Census sampling technique was used and the sample size was 78. A structured questionnaire was used for data collection. Descriptive and inferential statistics (Chi-square) was used for analysis. The level of significance (p) was set at 0.05.Results: The mean age of the participants was 19.5 years. Majority (67.9%) of the participants were male and the remaining 32.1% were female. Most (87.2%) of them had never donated blood. Few (38.5%) of them had history of blood requirement in the family whereas, 23.1% had blood donation in family. More than half (51.3%) of participants had inadequate level of knowledge regarding blood donation. The study showed that sex (p=0.04), history of self-blood donation (p=0.03) and history of blood requirement in the family (p=0.01) were found statistically significant with level of knowledge regarding blood transfusion.Conclusion: This study showed that majority of the students had inadequate knowledge regarding blood donation. Thus, it is very important to adopt strategies to sensitize and motivate them towards voluntary blood donation.